EFFECTIVE USE OF MONOCLONAL ANTIBODIES AGAINST TNF — ADALIMUMAB — AS A SWITCHOVER DRUG IN A PATIENT WITH JUVENILE IDIOPATHIC POLYARTHRITIS AND UVEITIS - S. A. Ushakova; N. L. Ashcheulova; L. N. Koneva; O. Yu. Khalidullina; O. V. Pavlova; V. S. Rezenova; V. N. Luk'yanova; E. E. Fedorova; M. V. Pshenichkova (Педиатрическая фармакология)
The article presents a case of severe juvenile idiopathic arthritis associated uveitis in a patient who contracted the disease at the age of 10 year. Uveitis developed 9 months after manifestation of the articular syndrome in the event of etanercept therapy. Switch to adalimumab induced remission of the articular syndrome and uveitis. By the 8th week of treatment, an inactive disease stage (6 months) was diagnosed in a child.